Implementation of Good Corporate Governance Principles in the Jakarta Smart Program (KJP Plus) in the New Normal Era - Angga Sulaiman; Bhakti Nur Avianto; Shalilha Shalilha (Journal Research of Social Science, Economics, and Management, 2022)
The Jakarta Smart Plus Card (KJP Plus) is a strategic program to provide access for DKI Jakarta residents from the underprivileged community to receive a minimum education until completing SMA or SMK with total funding from the DKI Jakarta Province APBD funds. The purpose of KJP Plus, as stated in the DKI Provincial governor regulation Number 15 of 2015 Article 3, that KJP Plus aims to: 1) Support the implementation of the 12 Year Compulsory Education; 2) Increasing access to education services fairly and equitably; and 3) Ensuring certainty of access to education services and improving the quality of education outcomes. This study aims to explore applying the principles of Good Corporate Governance (GCG) in the Jakarta Smart Plus Card (KJP Plus) program at SMKN 20 Jakarta during the COVID-19 pandemic. This research uses qualitative or descriptive methods. Data collection was carried out utilizing observation, interviews, and documentation. The data analysis used was data reduction, data presentation, and conclusion. The results showed Good Corporate Governance (GCG) in the Jakarta Smart Plus Card (KJP Plus). Had implemented by State Vocational High School (SMKN 20) during Covid-19 because it implemented the principles of transparency, accountability, responsibility, independence and fairness.